Drone Swarm for Post-Wildfire Hot Spot Detection: Technology Assessment and PoC Demonstrator - Sende, Micha; Raffelsberger, Christian; Hayat, Samira; Köfler, Armin; Almer, Alexander (Proceedings of the International ISCRAM Conference, 2024)
Post-wildfire hot spots are a severe problem for fire fighters since they are hard to detect and can reignite fires. The tedious search can be greatly improved by using drones. However, developing and controlling an autonomous drone swarm is a challenging task. An assessment with domain experts reveals the suitability of drone swarms for hot spot detection. We develop a heterogeneous multi-drone system that can support fire fighters by creating thermal and visual aerial images and automating the hot spot detection process. During a joint exercise with a fire fighter brigade we demonstrate that the proposed system is able to autonomously search, detect, and report hot spots. Therefore it is able to speed up the search process while reducing the required number of personnel.